Analisis Implementasi dan Pengungkapan Good Corporate Governance di PT Bank Syariah Indonesia TBK Tahun 2021 – 2023 - Alfin Rizki Permana (AKUNTANSI 45, 2025)
This study aims to analyze the implementation of Good Corporate Governance (GCG) principles at Bank Syariah Indonesia (BSI). GCG is a corporate management system that upholds the values ​​of transparency, accountability, responsibility, independence, and fairness. Effective GCG implementation is important to maintain customer trust and encourage sustainable business growth, especially in the Islamic banking industry. This study uses a descriptive qualitative method with a literature study and documentation approach. The results of the analysis show that BSI has implemented GCG principles through a transparent organizational structure, periodic reporting, and supervision from various internal committees, including the Sharia Supervisory Board. The results of the assessment of the implementation of GCG at BSI during 2021-2023 consistently entered the predicate "Very Good" with an average disclosure of 90.13. The disclosure value increased from 2021 to 2023. However, indicators of dual positions and efforts to resolve legal problems were not found in 2021. The researcher suggests that BSI start increasing GCG disclosure information in its annual report related to dual positions and efforts to resolve legal problems.